New Antimicrobial Strategies to Treat Multi-Drug Resistant Infections Caused by Gram-Negatives in Cystic Fibrosis - Viola Camilla Scoffone; Giulia Barbieri; Samuele Irudal; Gabriele Trespidi; Silvia Buroni (MDPI AG, 2024)
People with cystic fibrosis (CF) suffer from recurrent bacterial infections which induce inflammation, lung tissue damage and failure of the respiratory system. Prolonged exposure to combinatorial antibiotic therapies triggers the appearance of multi-drug resistant (MDR) bacteria. The development of alternative antimicrobial strategies may provide a way to mitigate antimicrobial resistance. Here we discuss different alternative approaches to the use of classic antibiotics: anti-virulence and anti-biofilm compounds which exert a low selective pressure; phage therapies that represent an alternative strategy with a high therapeutic potential; new methods helping antibiotics activity such as adjuvants; and antimicrobial peptides and nanoparticle formulations. Their mechanisms and in vitro and in vivo efficacy are described, in order to figure out a complete landscape of new alternative approaches to fight MDR Gram-negative CF pathogens.